Perancangan Aplikasi Ensiklopedia Menggunakan Augmented Reality Berbasis Android - Yesmaya, Violitta; T., Jojo Dekapaswan; Aspurua, Kevin; Prasetyo, Ilham (Yayasan Petra Harapan Bangsa, 2018)
Smartphone is a device that is currently widely used by people, now many parents start to introduce smartphones to their children. By introducing a smartphone with the right application can provide general knowledge material that more attractive to children so that they can understand the material. The purpose of developing this application is to introduce encyclopaedias in the form of Augmented Reality to the public with the application of technology that can facilitate and attract interest in studying matters relating to plants, animals and vehicles. This study uses the waterfall methodology that includes 5 stages: requirements analysis and definition, system and software design, implementation and unit testing, integration and system testing, operation and maintenance. Vuforia is an application to identify markers that are useful in scanning markers. The results of this application development are applications that can be run on the Android platform that can be used by users as teaching tools and can be used by parents as an introduction to basic materials for their children.Telefon genggam pintar merupakan perangkat yang saat ini banyak digunakan oleh semua kalangan masyarakat. Saat ini sudah cukup banyak orang tua yang mengenalkan telefon genggam pintar (smartphone) kepada anak-anak. Dengan memperkenalkan smartphone dengan aplikasi yang tepat dapat memberikan materi pengetahuan umum yang lebih menarik bagi anak-anak sehingga mereka dapat memahami materi. Tujuan dari pengembangan aplikasi ini adalah untuk memperkenalkan ensiklopedia dalam bentuk Augmented Reality kepada masyarakat dengan penerapan teknologi yang dapat mempermudah dan menarik minat untuk mempelajari hal-hal yang berkaitan dengan tumbuhan, hewan, dan kendaraan. Penelitian ini menggunakan metodologi waterfall yang meliputi 5 tahap: requirement analysis and definition, system and software design, implementation and unit testing, integration and system testing, dan operation and maintenance. Vuforia merupakan aplikasi untuk mengindentifikasi marker yang berguna dalam scanning marker. Hasil dari pengembangan aplikasi ini adalah aplikasi yang dapat dijalankan di platform Android yang dapat digunakan oleh pengguna sebagai perangkat ajar dan dapat dipakai oleh orang tua sebagai pengenalan materi dasar untuk anak-anaknya.